Weight loss maintenance of participants from weight loss program in Klinik Kesihatan Beserah, Kuantan after one year – was it a success? - Abdul Alam, Nur Amirah; Mamat, Nik Mazlan (2013)
The objective of this study was to investigate on weight lost achieved by participants in Weight Loss Program in Klinik Kesihatan Beserah (KKB) and to find the percentage of successful weight maintainers for at least 1 year after the program. A total of 34 participants who had successfully lost at least 5% of their initial weight after the 6 months program were identified from the database. Further selection in accordance to inclusion and exclusion criteria were made which result in a total of 16 participants (4 men and 12 women) aged 47.4 ± 10.2 years (range at 33 and 67 years) eligible for the study purpose and agreed to involve in. By using a structured questionnaire participants were interviewed for their weight history (initial weight, weight at the end of the program, and weight after 1 year of the program). The result showed that all participants successfully lost between 3.0 kg – 24.0 kg during the program, with Q2 of 6.55kg. A total of 43.8% of the subjects successfully maintained the weight lost after one year. From the successful weight lost maintainers, 57.1% continues to lose their weight while 42.9% just maintain the weight as achieved at 6 months. Investigation on strategies practiced to achieve weight maintenance found that 71.4% of weight-loss maintainers attributed their success on good dietary control, while increased in physical activity and behavior changes is perceived to be moderately effective. From this study it shows that, dietary understanding and practice gives a more significant impact in weight maintenance rather than the role of physical activity and behavioral changes. In addition, a structured weight loss program shows to be effective in weight management even after the completion of the program.